Ridley. Season one [videorecording (DVD)] - Fisher, Jonathan (Producer); Thompson, Paul Matthew (Ridley, 2023)
Retired Detective Alex Ridley is lured back into service as a consultant detective when his former protégé, Carol Farman, needs help cracking a complex murder case.